Assessing farmers’ willingness-to-way for improved common bean seed varieties in Malawi : a case study of Kasungu and Dedza districts - Liebenberg, Frikkie (University of Pretoria, 2014)
Dissertation (MSc Agric)--University of Pretoria, 2013.